Literature Review: Risk Factors of Pulpitis Incidence in Coastal Areas - Wulan Rewangi; La Ode Muhammad Jems Trailing Labalue (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Pulpitis is an inflammatory condition of the dental pulp, the innermost part of the tooth that contains nerves, blood vessels, and connective tissue. This condition is most commonly caused by bacterial infection resulting from untreated dental caries, although it may also occur due to physical trauma, chemical irritation, or improper restorative procedures. Inflammation within the pulp increases intra-pulpal pressure in the confined pulp chamber, thereby impairing blood circulation and oxygen supply. If left untreated, this process can lead to irreversible tissue damage or pulp necrosis. Dental caries remains the primary etiological factor for pulpitis. According to the 2018 Riset Kesehatan Dasar (RISKESDAS), approximately 88.8% of the Indonesian population experiences dental caries. Individuals residing in rural coastal communities are particularly vulnerable due to inadequate oral hygiene practices such as infrequent or improper tooth brushing and high consumption of carbohydrate- and sugar-rich foods, which can precipitate pulpitis. Furthermore, limited access to dental healthcare services in these areas results in a high prevalence of untreated dental caries, increasing the risk of progression to pulpitis. A lack of awareness and education on oral health further exacerbates this burden.Objective: This literature review aims to identify and describe the risk factors contributing to the incidence of pulpitis in rural coastal communities.Methods: This study employed a systematic literature review approach. Articles were identified through searches on Google and Google Scholar using the keywords